Estrategias de gamificación en el desarrollo del pensamiento lógico matemático, primero de bachillerato, Unidad Educativa Tabacundo, periodo 2021-2022 - Cabezas Espinoza, Anderson Fernando (2023)
Gamification is a strategy that allows adding learning activities favoring student participation and motivation. Its main problem to investigate is how gamification strategies influence the development of mathematical, logical thinking in students. The present pre-experimental design research aims to study the effect produced by the application of gamification strategies in the development of mathematical, analytical thinking in a group of 43 first-year high school students, from the Tabacundo Educational Unit, during the period 2021. -2022. Initially, a mathematical, logical thinking test was applied and evaluated on 20 points, which contained four sections, consisting of solving problems such as sequences, rule of three, counting and combinatorics, and algebraic equations. The results of the pre-test reflected that most students presented difficulties in developing mathematical and logical thinking, with an average of 9.31 out of 20 points. Then, gamification strategies were applied for four weeks through bingo, number games, magic mate, and visual games. After implementing the proposal, the post-test of Mathematical Logical Thinking was involved again, where the average score rose to 13.82 out of 20. Through the t-student statistical hypothesis test for related samples, it was proven that there is a significant improvement in the resolution of succession problems, rule of three, counting and combinatorics, and algebraic equations. Therefore, it was shown that gamification strategies favorably influenced the development of mathematical, logical thinking.